The patient's pathway for breast cancer in the COVID‐19 era: An Italian single‐center experience. Issue 8 (28th June 2020) - Casella, Donato; Fusario, Daniele; Cassetti, Dario; Miccoli, Simone; Pesce, Anna Lisa; Bernini, Andrea; Marcasciano, Marco; Lo Torto, Federico; Neri, Alessandro
Abstract: COVID‐19 has been declared a pandemic by the World Health Organization. As of April 1, 2020, Italy was the country with the second highest number of cases in the world. The spread of COVID‐19 has required a rapid reorganization of health service delivery in face of the pandemic. Breast cancer units have reprioritized their workload to guarantee the health of oncologic patients at the highest risk and regular screening activities. However, at the end of the pandemic emergency, many benign and reconstructive cases will return to our attention and their surgical treatment will be necessary as soon as possible.